Unsur Hiperrealitas dalam Video Iklan Parfum Guerlain: L’homme Idéal - Lahuda, Dea Nur; Huntley, Myrna Laksman (UI Scholars Hub, 2021)
The glance of perfume advertising found in the previous study has two main themes: visual and verbal strategies. Video advertisement of Guerlain brand perfume from France for his latest male series, L’Homme Idéal, displayed containing both themes referred to the domination of monochrome colors and the narration of the explanation of perfume itself uploaded through YouTube social media. This study examines metaphors and signs in an advertisement to see how far the advertisement affects people’s minds in playing with their imagination, using a qualitative method and literature studies as a data collection technique. The analysis uses Kövecses’s metaphorical theory, Peirce’s semiotics, and Baudrillard’s hyperreality and is supported seven informants’ input. It is found that seductive language in the form of metaphors succeeded in attracting male consumers. Various signs are also found to help the metaphor visualize the ideal image of masculinity through handsomeness, intelligence, and strength. Combining these two types of themes in the depiction of lifestyle and the explanation of the perfume smell in this video advertisement has a great potential to affect people in achieving hyperreality.